ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN SEKTOR PERTANIAN DI BURSA EFEK INDONESIA - jontro SIMANJUNTAK (JURNAL AKUNTANSI BARELANG, 2018)
This study aims to determine the effect of fundamental factors such as earnings per share, debt to equity ratio, and return on equity to stock returns in agricultural companies listed on the Indonesia Stock Exchange. The population in this study are all companies listed on the Indonesia Stock Exchange in the period of research in 2012 until 2016 which amounted to 24 companies and samples in this study amounted to 11 companies obtained by using purposive sampling method. The research tool used is SPSS (Statistical Product and Service Solutions) version 21. The research method used is multiple linear regression analysis and hypothesis test using t-test to measure the partial regression coefficient and F-test to test the influence of independent variables simultaneously. The results of this study indicate that earning per share partially have a negative but not significant effect on stock returns. Debt to equity ratio and return on equity partially have positive but not significant effect to stock return. Earning per share, debt to equity ratio, and return on equity simultaneously have no significant effect on stock return.